4-phenylbutyric acid promotes migration of gastric cancer cells by histone deacetylase inhibition-mediated IL-8 upregulation. Issue 6 (2nd July 2020) - Shi, Xiaonan; Gong, Libao; Liu, Yunpeng; Hou, Kezuo; Fan, Yibo; Li, Ce; Wen, Ti; Qu, Xiujuan; Che, Xiaofang
ABSTRACT: Histone acetylation is regulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs). It is associated with gene transcription and expression. 4-Phenylbutyric acid (4-PBA), an HDAC inhibitor (HDACi), can inhibit cancer cell proliferation by increasing the level of histone acetylation. However, 4-PBA did not show any efficacy in clinical trials. In this study, we found that 4-PBA induced epithelial–mesenchymal transition (EMT) in gastric cancer cell lines MGC-803 and BGC-823 with ectopic E-cadherin expression. Based on the expression profile microarray, IL-8 was the most significantly up-regulated gene by 4-PBA, and was selected for further investigation. Knockdown of IL-8 partially prevented 4-PBA-induced-EMT by blocking the activation of the downstream Gab2-ERK pathway. Furthermore, CHIP assay confirmed that acetyl-H3 directly combined with the promoter region of IL-8 to promote its transcription. Therefore, the results of this study demonstrated that 4-PBA-mediated inhibition of HDAC activity could induce EMT in gastric cancer cells via acetyl-histone-mediated IL-8 upregulation, and the downstream Gab2/ERK activation. These data indicated the possible reason for the failure of 4-PBA in clinical trials.